2021
DOI: 10.2139/ssrn.3813161
|View full text |Cite
|
Sign up to set email alerts
|

Facing the 'New Normal': How Adjusting to the Easing of COVID-19 Lockdown Restrictions Exposes Mental Health Inequalities

Abstract: BackgroundIn March 2020, the UK Government enforced its first national 'lockdown' in response to the COVID-19 pandemic. Significant restrictions to the lifestyle and conduct of the public were enforced, including institution of various safety-behaviours such as washing, mask-wearing and physical distancing, aimed at reducing the spread of infection. From July -November 2020, as infection rates dropped, a gradual easing of restrictions occurred in most parts of the country alongside a short-lived restoration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…For first aim of the present study, as predicted, the results showed that all the measured indices were different before and during the pandemic, lower levels of physical activity and self-esteem and higher levels of social anxiety from before to during the COVID-19. The findings indicating detrimental effects of the COVID-19 pandemic on the levels of physical activity and of psychological indicators are in line with previous studies [ 6 , 15 , 29 31 , 33 , 34 ]. For example, Di Franco et al [ 10 ] in their study examined the effects of social distance on mental health status and physical activity during the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…For first aim of the present study, as predicted, the results showed that all the measured indices were different before and during the pandemic, lower levels of physical activity and self-esteem and higher levels of social anxiety from before to during the COVID-19. The findings indicating detrimental effects of the COVID-19 pandemic on the levels of physical activity and of psychological indicators are in line with previous studies [ 6 , 15 , 29 31 , 33 , 34 ]. For example, Di Franco et al [ 10 ] in their study examined the effects of social distance on mental health status and physical activity during the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, we tried to pay attention to these physical and psychological variables and evaluate the impact of the COVID-19 pandemic on them. To date, however, much research has been conducted worldwide on the impact of the COVID-19 pandemic on levels of physical activity and mental health [ 6 , 29 31 ]. Also, to our knowledge, there is little information about this, especially for Iran [ 32 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…• Clinicians in general, including urologists, should be aware of the suicide risk associated with OCD, especially in those with severe obsessions wake of the COVID-19 pandemic, possibly owing to prolonged exposure to statutory reinforcement of safety behaviours. 12 Therefore, it is increasingly important for clinicians in general to be aware of the diagnosis and feel confident to sensitively enquire about it.…”
Section: Key Pointsmentioning
confidence: 99%
“…Consequently, there may be a delay between the onset of the disturbance and the onset of treatment, which can adversely affect the clinical outcome 11 . Moreover, emerging evidence suggests that the prevalence of OCD among the general population and the severity of obsessive‐compulsive symptoms may be increasing in the wake of the COVID‐19 pandemic, possibly owing to prolonged exposure to statutory reinforcement of safety behaviours 12 . Therefore, it is increasingly important for clinicians in general to be aware of the diagnosis and feel confident to sensitively enquire about it.…”
mentioning
confidence: 99%
“…Others areas that have been impacted include both domestic and international travel, self-assessment, isolation at home and testing (when needed), and maintaining close contact with the COVID-19 support infrastructure in case of emergency (Ingrassia et al, 2020;Owan, Asuquo, Ekaette, et al, 2021). Other new normal behaviors include regular handwashing, covering the mouth and nose when coughing, regularly cleaning surfaces, monitoring, and self-isolation for those people exposed or feeling unwell (Fineberg et al, 2021). As a result, it is reasonable to consider that people would alter their habits and routines in order to conform to the new standards.…”
Section: Introductionmentioning
confidence: 99%